PENGARUH MEDIA “SMART STAIR” PADA OPERASI HITUNG PENJUMLAHAN DAN PENGURANGAN TERHADAP HASIL BELAJAR SISWA KELAS 1 MI DARUL AKHYAR - Dea Kiki Yestiani; Een Unaenah; Nelly Manik (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study uses a quantitative method used is the Quasi method Experiment. The population subjects in this study were 1st grade students of MI Darul Akhyar, totaling 57 students. By taking a sample of two classes, class 1C 30 students as the control class and class 1B 27 students as the experimental class. Pretest in the control and experimental classes. Hypothesis testing was carried out using the t test with a significant level of ∞ = 0.05 for n = 55 in the experimental and control classes. Because the results of data processing are obtained t_(count) = -3.8 and t_(table) = 0.70 because t_(count) < t_(table) then H_0 is accepted. Thus at the beginning of learning there is no effect on student learning outcomes between the experimental and control classes. While the hypothesis is carried out using the t test with a significant level of ∞ = 0.05 for n = 55 in the control class and the experimental class. Because the data is normal and homogeneous, dk = n_1 = n_2 – 2. Based on the results of data processing, it is obtained t_(count)=2.51 and t_(table) = 0.01 because t_(count)> t_(table) then H_1 is accepted. Thus at the end of learning there is an influence on student learning outcomes between the experimental and control classes.